Tamar (2 Sam 13:1-22) – a beacon of wisdom amidst a sea of madness - Celarc, Matjaž (Bogoslovni vestnik, 2025)
This article offers a narrative-theological reading of Tamar’s story in 2 Sam 13:1-22, situating it within the Davidic narrative and the broader biblical canon. Far from being an isolated tragedy, Tamar’s violation marks the first fracture in the royal household, fulfilling Nathan’s oracle in 2 Sam 12:10-11 and exposing the systemic collapse of Davidic authority. A close literary analysis – attending to structure, repetition, and key Hebrew terms such as ??????? (outrage), ?? ??? ??? ???? ??? ??? (a long robe), and ???????? (desolation) – shows how Tamar’s embodied lament becomes a prophetic protest. Her gestures of mourning – tearing her robe, scattering ashes, placing her hand upon her head, and crying aloud – name injustice and preserve dignity when her father and brothers fail to act. Read intertextually, Tamar’s story resonates with Esther (Esth 4:17 LXX), Susan-na (Dan 13), and the woman accused of adultery (John 8:1-11). Each of these narratives portrays women confronting systemic injustice; together they highlight lament as a form of agency that unmasks patriarchal power while anticipating divine justice. Unlike Susanna, whose cry is vindicated, Tamar’s protest remains unanswered, embodying the silence of failed kingship. By contrast, in John 8 Jesus becomes the woman’s advocate, restoring dignity through mercy rather than condemnation. Drawing on feminist, narrative-critical, and trauma hermeneutical approaches, the article argues that Tamar is more than a tragic victim. She emerges as a beacon of wisdom amid a collapsing household and a prophetic witness within Israel’s story. Her memory testifies that God hears the silenced and that lament can become the seed of truth, dignity, and hope.
Keywords: 2 Sam 13; Davidic monarchy; Davidova monarhija; intertekstualnost; intertextuality; lament; preroška priča; prophetic witness; sexual violence; spolno nasilje; Tamar; žalovanje